SIKAP PETANI PADI ORGANIK TERHADAP PROGRAM OVOP (ONE VILLAGE ONE PRODUCT) BERBASIS KOPERASI PRODUK BERAS ORGANIK - Sendy Chistina Kusumawardhani; Bekti Wahyu Utami; Widiyanto Widiyanto (Universitas Sebelas Maret, 2016)
This research aims to examines the factors forming attitudes of the farmer, it examines the attitudes of farmers toward OVOP Program, and examines the correlation between the factors forming attitudes with the attitudes of farmers toward OVOP Program in Karanganyar Regency. This research was carried out by using a descriptive method. The research location is determined purposively. The sampling technique is proportional random sampling with 40 respondents from two cooperations are KKT Tani Makaryo and KSU Anugerah Jaya. Method of analysis used to determine the correlation of the factors forming attitudes with the attitudes of farmers toward OVOP Program is the correlation coefficient of Rank Spearman. Result of the research indicate that other’s influence factor have a very significant correlation. Farming experience, formal education, and non formal education have a significant correlation. Age, mass media, cultural of nature conservation and income don’t have a significant correlation.